Factor XI Inhibitors for Prevention and Treatment of Venous Thromboembolism: A Review on the Rationale and Update on Current Evidence - Nopp, Stephan; Kraemmer, Daniel; Ay, Cihan (Frontiers in Cardiovascular Medicine, 2022)
Although anticoagulation therapy has evolved from nonspecific drugs (i.e., heparins and vitamin K antagonists) to agents that directly target specific coagulation factors (i.e., direct oral anticoagulants, argatroban, fondaparinux), thrombosis remains a leading cause of death worldwide. Direct oral anticoagulants (i.e., factor IIa- and factor Xa-inhibitors) now dominate clinical practice because of their favorable pharmacological profile and ease of use, particularly in venous thromboembolism (VTE) treatment and stroke prevention in atrial fibrillation. However, despite having a better safety profile than vitamin K antagonists, their bleeding risk is not insignificant. This is true for all currently available anticoagulants, and a high bleeding risk is considered a contraindication to anticoagulation. As a result, ongoing research focuses on developing future anticoagulants with an improved safety profile. Several promising approaches to reduce the bleeding risk involve targeting the intrinsic (or contact activation) pathway of coagulation, with the ultimate goal of preventing thrombosis without impairing hemostasis. Based on epidemiological data on hereditary factor deficiencies and preclinical studies factor XI (FXI) emerged as the most promising candidate target. In this review, we highlight unmet clinical needs of anticoagulation therapy, outlay the rationale and evidence for inhibiting FXI, discuss FXI inhibitors in current clinical trials, conduct an exploratory meta-analysis on their efficacy and safety, and provide an outlook on the potential clinical application of these novel anticoagulants.